Overview of Nurse Therapeutic Communication in Hospital Ward PKU Muhammadiyah Gamping - Siti Ina Maitoh; Yuni Kurniasih; Rosiana Nur Imallah (Yayasan Lentera Mitra Lestari, 2026)
Background: Therapeutic communication has become the main key to delivering nursing care. Therapeutic communication plays an important role in raising trust, increasing comfort, and helping patients express their needs and complaints during treatment. However, nurses do not practice therapeutic communication well and do not pay attention to the quality of the communication they implement. Objective: This study aims to describe the quality of nurses' therapeutic communication in PKU Muhammadiyah Gamping Hospital. Methods: This study adopted a descriptive design, involving 96 respondents selected using purposive sampling. Data were collected using structured questionnaires to assess therapeutic communication. Data analysis was performed using a univariate test. Result: Respondent majority female (36.5%) and domination by 40-50 years old (57.3%). Most nurses had good therapeutic communication with their patients (66.7%). Conclusion: The quality of therapeutic communication helps improve nursing care delivery. The average therapeutic communication skills in this study were classified as good.